Menciptakan Generasi Peduli Lingkungan: Inovasi Ekokurikulum Berbasis Kearifan Lokal Madura di SMP Pamekasan - Putikadyanto, Agus Purnomo Ahmad; Wachidah, Liana Rochmatul; Sari, Sifa Yunita (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2024)
The present curriculum emphasizes contextual learning, which can be used to shape a generation that appreciates the environment and develops character based on ecological principles. The purpose of this study is to describe the innovation of implementing Madurese local wisdom eco-curriculum at Pamekasan Middle School. This study uses a qualitative research method. The data sources for this study were 4 principals of Pamekasan Middle Schools, the deputy head of curriculum, teachers, and students. The research data were in the form of observation results, interviews, and documentation. The results of this study are (1) the preparation of an independent curriculum with Madurese local wisdom integrated with environmental values â€‹â€‹at Palengaan 2 Middle School, Larangan 1 Middle School, Pameksan 4 Middle School, and Groâ€™om Middle School, which includes a series of systematic and planned steps, starting from learning planning to developing teaching modules. Awareness of the importance of protecting the environment can be instilled through a learning approach that is relevant to the local context. All activities are designed by considering the Learning Components, Learning Objectives, and Learning Tools. The challenges faced are very diverse and complex, covering various aspects that affect the effectiveness of curriculum implementation. The potential of the Merdeka Curriculum with Madura’s local wisdom in creating a generation that cares about the environment is significant. This is reflected through cultural values, which are needed to become agents of change who are committed to environmental conservation.